Financial liberalization and stock markets integration for Asean-5 countries - Sew-Ming Phuan; Kian-Ping, Lim; Ai-Yee Ooi (Canadian Center of Science and Education, 2009)
This paper examines the relationship of financial liberalization and stock markets integration among ASEAN-5 (Note 1) stock markets: Indonesia, Malaysia, the Philippines, Singapore and Thailand. Three sample periods are covered based on the progress of financial liberalization. By using Johansen and Joseluis multivariate cointegration procedures, Granger-causality tests and variances decomposition analysis, the results indicate no long-run relationship during Singapore stock market liberalization in the first period. However, long-run relationship established between ASEAN-5 stock markets in the second period when Thailand, Malaysia and Indonesia have liberalized their stock markets and the third period following the Philippines liberalization. The long run integration relationships and the short-run causality relationships among ASEAN-5 markets have both increased after the financial liberalization. Thailand, Malaysia, Indonesia and the Philippines markets have received increased influences from other stock markets in the progress of financial liberalization whereas Singapore remains unaffected by the others. Stock markets that liberalize earlier will have greater influence on other stock markets.